Radio frequency energy harvesting sources - Nechibvute, Action; Chawanda, Albert; Taruvinga, Nicholas; Luhanga, Pearson (De Gruyter Open, 2018)
This radio frequency (RF) energy harvesting is an emerging technology and research area that promises to produce energy to run low-power wireless devices. The great interest that has recently been paid to RF harvesting is predominantly driven by the great progress in both wireless communication systems and broadcasting technologies that have availed a lot of freely propagating ambient RF energy. The principle aim of an RF energy harvesting system is to convert the received ambient RF energy into usable DC power. This paper presents a state of the art concise review of RF energy harvesting sources for low power applications, and also discusses open research questions and future research directions on ambient RF energy harvesting.